Eastern immigrants strategies in spain during the economic crisis - Viruela, Rafael; Marcu, Silvia (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
The Great Recession, which began in late 2007, is manifested primarily as employment crisis and mainly affects the immigrant population. Most immigrants have decided to remain in Spain, and to mitigate the effects of the crisis, several strategies have been deployed in the productive and reproductive spheres. One response to the progressive degradation of the labor market has been the internal and transnational geographical mobility, which takes various strategies: return to the country of origin, migration to a third country, and circular migration. The information used in this article comes from in-depth interviews to 64 citizens of Romania and Bulgaria residing in Spain, as well as from and 32 other interviews to family members and returnees, which took place in their countries. To the information coming from the emigrants we add socioeconomic data provided by the National Institute of Statistics and the Ministry of Employment.